2017
DOI: 10.1016/j.jnc.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Environmental attitudes and preference for wetland conservation in Malaysia

Abstract: The incorporation of latent psychological factors in wetland valuation studies may improve our understanding of why some people value ecosystem services while others do not. This article focuses on public preferences for enhanced protection of the Setiu Wetland in Malaysia and explores the influence of environmental attitude on preference and the willingness to pay (WTP) for wetland conservation. The study reported here employs a discrete choice experiment to investigate household's WTP for a set of wetland at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…Crompton showed that attitudes influence tourists' choices of destinations, and the intrinsic motivation of tourists' values and interests can generate higher intention to visit a destination [27,28]. Suziana also showed that biosphere-centered people have an active visual preference for biodiversity [29]. We found that eco-society-hedonic tourists pay more attention to the biosphere environment and have a strong visual preference for wetland park plants.…”
Section: Discussionmentioning
confidence: 61%
“…Crompton showed that attitudes influence tourists' choices of destinations, and the intrinsic motivation of tourists' values and interests can generate higher intention to visit a destination [27,28]. Suziana also showed that biosphere-centered people have an active visual preference for biodiversity [29]. We found that eco-society-hedonic tourists pay more attention to the biosphere environment and have a strong visual preference for wetland park plants.…”
Section: Discussionmentioning
confidence: 61%
“…The WTP for FSPS of the respondents in Cigu, Taiwan is lower than that in other countries. Moreover, Suziana [43] showed that the concern regarding the environmental issues of a Malaysian wetland influences respondents' WTP; hence, this study believes that the respondents' concern regarding environmental issues will influence their WTP for the development of FSPS.…”
Section: Combination Of Choices Preferred By Respondentsmentioning
confidence: 84%
“…Biodiversity reflects the range and diversity of animals and plants in the wetland and is often used as an indicator for assessing coastal ecosystems [33,35,38]. Suziana [43] adopted CEM to discuss the conservation of the Malaysian wetland ecosystem, with attributes including environmental conditions, biodiversity, recreational services, flood control, and subsidy changes. The FSPS policy to be implemented by the Taiwan government pays attention to developing green energy generation facilities without affecting the existing fishery production, and ensuring that the aquaculture production environment is optimized to reduce the labor input.…”
Section: □ □ □mentioning
confidence: 99%
“…Considering the relevance of the attributes, many studies differentiate between demand relevance and policy relevance (Blamey et al 1997;Abiiro et al 2014;Armatas et al 2014;Suziana 2017). The relevance of attributes is hence divided into two different aspects: 1) attributes are important to the respondents (demand relevance) and 2) attributes can be impacted by policy (policy relevance).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Armatas et al (2014) and Kløjgaard et al (2012) used the concept of importance and emphasized the process of selecting important goods and attributes for respondents. According to Suziana (2017), 'demand-relevant attribute is the attribute that has meaning for those interviewed.' In turn, attributes have policy relevance when they are relevant to policy makers and can be affected by policy decisions.…”
Section: Introductionmentioning
confidence: 99%